Comparative Assessment of Response to Cadmium in Heavy Metal-Tolerant Shrubs Cultured In Vitro - Wiszniewska, A. (Water Air Soil Pollut, 2017)
Two species of Pb-adapted shrubs, Alyssum montanum and Daphne jasminea, were evaluated in vitro for their tolerance to elevated concentrations of cadmium. Shoot cultures were treated with 0.5, 2.5, and 5.0 μM CdCl(2) for 16 weeks and analyzed for their organogenic response, biomass accretion, pigment content, and macronutrient status. Cadmium accumulation and its root-to-shoot translocation were also determined. In both species, rooted microplantlets, suitable for acclimatization, were obtained in the presence of Cd applied as selection agent. In A. montanum, low and moderate dose of Cd stimulated multiplication, rooting, and biomass production. Growth tolerance index (GTI) in Cd-treated shoots ranged from 120 to 215%, while in the roots 51–202%. In turn, in Cd-treated D. jasminea proliferation and rooting were inhibited, and GTI for shoots decreased with increasing doses of Cd. However, roots exposed to Cd had higher biomass accretion. Both species accumulated Cd in developed organs, and its content increased with increasing CdCl(2) dose. Interestingly, D. jasminea accumulated higher amounts of Cd in the roots than A. montanum and immobilized this metal in the root system. On the contrary, A. montanum translocated some part of accumulated Cd to the shoots, but with low efficiency. In the presence of Cd, A. montanum maintained macronutrient homeostasis and synthesized higher amounts of phytosynthetic pigments in the shoots. D. jasminea accumulated root biomass, immobilized Cd, and restricted its translocation at the expense of nutrient balance. Considering remediation potential, A. montanum could be exploited in phytoextraction, while D. jasminea in phytostabilization of polluted substrate.